Short Communication: Description and molecular diagnosis of a new species of Delphinium (Ranunculaceae) from Northeast Iran - MASOOMEH HASANBARANI; FARIBA SHARIFNIA; TAHER NEJADSATTARI; MOSTAFA ASSADI (Society for Indonesian Biodiversity, 2017)
Hasanbarani M, Sharifnia F, Nejadsattari T, Assadi M. 2017. Short Communication: Description and molecular diagnosis of a new species of Delphinium (Ranunculaceae) from Northeast Iran. Biodiversitas 18: 639-644. Delphinium khorasanicum Sharifnia & Hasanbarani sp. nov., a species distributed in NE Iran, is described and provided with a molecular diagnosis. It is morphologically related to D. turkmenum Lipsky. The most important morphological differences between the new species and D. turkmenum are mainly in the shape of spur, plant length and epidermal patterns. This species is compared with close taxa (they are close and relative in point of view morphologically, geographically and molecular characters). Illustration and distribution map are also presented.